Comparative facilitation of activated carbon and goethite on methanogenesis from volatile fatty acids. (April 2020) - Xu, Suyun; Zhang, Wanqiu; Zuo, Liuquan; Qiao, Zihao; He, Pinjing
Highlights: Both AC and goethite improved methane yield under acid stress. Promoting effect of goethite on methanogenesis was more significant than AC. Goethite is conducive to the activation of iron-containing enzymes. Selective enrichment of Syntrophomonadaceae is associated with higher EDC value of Goethite. Abstract: To provide insight into direct interspecies electron transfer (DIET) via carbon-based materials and ferric oxides, the effects of three conductive materials (i.e. activated carbon (AC), iron modified activated carbon (FEAC) and goethite (FEOOH)), on methanogenesis from volatile fatty acids (VFAs) were evaluated. Under the acid stress ( 4 g/L VFAs), the maximum methane yield of 266 mL/g-chemical oxygen demand (COD) was found in the FEOOH supplemented reactor, which was 48% higher than that of AC reactor. The reasons for the enhanced activity of the electron transport chain and extracellular electron transfer ability by FEOOH include: 1) the activation on iron-containing enzymes that involved in methanogenesis and acidogenesis; 2) selective enrichment on functional microorganism. The higher electron donating capacities (EDC) value of FEOOH may be a triggering factor on the growth of Syntrophomonadaceae, which perform DIET with methanogens ( Methanosaeta and Methanosarcina ) for the syntrophic degradation of VFAs.